Turkey as A Determinant Factor Stabilizing the Middle East - Shokhan Sherzad Qader; Mohammed Ihsan (QALAAI ZANIST JOURNAL, 2020)
The aim of this study is to identify whether Turkey can be a determinant factor in stabilizing the Middle East. The role of Turkey as a regional power has increased from the time Justice and Development Party (JDP) ascended to power. The leadership of JDP did not just aspire to be a regional power but a global power. Thus, Turkey assumed various roles, like being an accepted leader within the region, a big brother historically, plus a shield of Muslim subgroups. Other roles that Turkey has obtained are those of a facilitator and mediator with its attempt to create stability within Iraq, Syria, and within the entire Middle East. The method that was used in gathering the research is qualitative and use of secondary sources. Sieving through the previous works conducted by other authors, the researcher managed to obtained relevant material and used it to contextualize the study and explain how Turkey is playing an eminent role in stabilizing the Middle East. In light of the current research study, Turkey has made various efforts in improving relations with its Neighbors and has played a mediator role within the Middle East. Through foreign policy, Turkey has bolstered good relations within Middle East. To enhance stabilization in the Middle East, Turkey ought to maintain the good relations with various countries embrace the challenges emanating from its role. Ideally, good relationships in the political realm provide a favorable environment for countries that seek to unite warring nations. Hence, Turkey should ensure good relations to bolster stabilization in the Middle East. The contribution of this research paper lies within the analysis bringing the wide range of descriptions in the literature together, discovering samples and examples regarding Turkey as a mediator role since JDP government, and tried to bring all of these literature in a piece of work, therefore this would be a path for other researchers to study and analyze more in future studies.